PENATALAKSANAAN FISIOTERAPI PADA KASUS BELL’S PALSY - Sofyan, Muhammad; Haryatno, Pajar; Kurniawati, Dwi (PHYSIO MOVE JOURNAL, 2024)
Bell's palsy is a sudden onset weakness of one side of the face due to damage to the facial nerve classified as a neurologicaldisorder. Typical changes in the face with Bell's palsy can hinder functional daily activities such as: eating, drinking, and talking to others. The alleged causes of Bell's palsy are vascular ischemic, viral, bacterial, hereditary, and immunological. Objective: to determine how physiotherapy management in Bell's palsy cases to improve facial motor function ability and facial muscle strength. Method: infra red, massage, and mirror exercise which is done for 3 times therapy. Result: there is an increase in facial motor function from T1 with a total score of 54 (moderate) increasing to T3 therapy with a total score of 70 (good) and an increase in facial muscle strength from T1 with a value of 1 increasing to T3 with a value of 3. Conclusion: Patients with the initials Mrs. L, 54 years old with a diagnosis of Bell's palsy sinistra after getting physiotherapy actions for 3 times obtained the results of an increase in facial motor functional abilities and increased facial muscle strength.Keywords: Bell’s palsy, infra red, massage, mirror exercise